Effect of Time after Anterior Cruciate Ligament Tears on Proprioception and Postural Stability - Lee, Dae-Hee (PLoS One, 2015)
This study was designed to compare proprioception and postural stability in patients with acute (time from injury ≤ 3 months) and chronic (time from injury > 3 months) ACL tears, and to evaluate the correlation between time interval after ACL injury and proprioception. Thigh muscle strength, postural stability, and joint position sense were compared in 48 patients with acute ACL tears and in 28 with chronic ACL tears. Maximal torque (60°/sec) of the quadriceps and hamstring was evaluated using an isokinetic testing device. Postural stability was determined from the anterior-posterior (APSI), medial-lateral (MLSI), and overall (OSI) stability indices using stabilometry. Joint position sense was also tested by reproduction of passive positioning (RPP). Muscle strengths and stability indices on both the involved and uninvolved sides were similar in the acute and chronic ACL tear groups. RPP on the involved side was significantly greater in the chronic than in the acute ACL tear group (7.8° vs. 5.6°, P = 0.041). Two of three stability indices (APSI, OSI) and RPP were significantly greater on the involved than the uninvolved side in the chronic ACL tear group.